SOCIAL EFFECT OF SOCIAL MEDIA REVEALED IN THE SOCIAL DILEMMA DOCUMENTARY MOVIE: POST-TRUTH PERSPECTIVE - Iddianto Iddianto; Rahmawati Azi (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2022)
Social media has been a platform to create any social effect in society. Social media is not only utilized to spread useful information, but also misinformation, such as fake news, rumor bombs, and lying intentionally. The Social Dilemma is one of the movies that revealed the social effect of social media, such as; Twitter, Facebook, Tik-Tok, Youtube, and Instagram. These platforms become the center of spreading misinformation, particularly in the midst of pandemic Covid-19 by manipulating real facts and public opinion. This study tried to scrutinize the spreading of misinformation revealed in The Social Dilemma movie through the Post-Truth perspective. Post-Truth believed that the use of social media to disseminate misinformation is related to social, political, and economic interests. People no longer respect the truth but accept it based on what they feel and believe, and social media has become a useful tool to fulfill this function. This study attested that misinformation spread by several social media users and politicians caused social effects such as chaos in the midst of a pandemic, destruction of 5G network towers, the formation of new truths based on misinformation about Covid-19 as a hoax, and the formation of public opinion regarding the Democratic party as the spreader of the Covid-19 virus in the US.